Structural Basis for Potent Neutralization of Betacoronaviruses by Single-Domain Camelid Antibodies - Wrapp, Daniel; De Vlieger, Dorien; Corbett, Kizzmekia S.; Torres, Gretel M.; Wang, Nianshuang; Van Breedam, Wander; Roose, Kenny; van Schie, Loes; Hoffmann, Markus; Pöhlmann, Stefan; Graham, Barney S.; Callewaert, Nico; et al. (Cell, 2020)
Coronaviruses make use of a large envelope protein called spike (S) to engage host cell receptors and catalyze membrane fusion. Because of the vital role that these S proteins play, they represent a vulnerable target for the development of therapeutics. Here, we describe the isolation of single-domain antibodies (VHHs) from a llama immunized with prefusion-stabilized coronavirus spikes. These VHHs neutralize MERS-CoV or SARS-CoV-1 S pseudotyped viruses, respectively. Crystal structures of these VHHs bound to their respective viral targets reveal two distinct epitopes, but both VHHs interfere with receptor binding. We also show cross-reactivity between the SARS-CoV-1 S-directed VHH and SARS-CoV-2 S and demonstrate that this cross-reactive VHH neutralizes SARS-CoV-2 S pseudotyped viruses as a bivalent human IgG Fc-fusion. These data provide a molecular basis for the neutralization of pathogenic betacoronaviruses by VHHs and suggest that these molecules may serve as useful therapeutics during coronavirus outbreaks. [Display omitted] •VHHs isolated from a llama immunized with prefusion-stabilized coronavirus spikes•Structural characterization of VHHs reveals conserved mechanism of neutralization•SARS-CoV-1 S-directed VHH cross-reacts with SARS-CoV-2 S•Bivalent VHH neutralizes SARS-CoV-2 pseudoviruses Using llamas immunized with prefusion-stabilized betacoronavirus spike proteins, Wrapp et al. identify neutralizing cross-reactive single-domain camelid antibodies, which may serve not only as useful reagents for researchers studying the viruses causing MERS, SARS, and COVID-19, but also potential therapeutic candidates. Crystal structures further reveal how these antibodies bind spike proteins to prevent virus entry into cells.